Estimating carbon stocks of three traditional agroforestry systems and their relationships with tree diversity and stand density - ADISTI PERMATASARI PUTRI HARTOYO; SALMA KHAIRUNNISA; PRIJANTO PAMOENGKAS; ACHMAD SOLIKHIN; SUPRIYANTO SUPRIYANTO; ISKANDAR Z. SIREGAR; LILIK BUDI PRASETYO; ISTOMO ISTOMO (Society for Indonesian Biodiversity, 2022)
Abstract. Hartoyo APP, Khairunnisa S, Pamoengkas P, Solikhin A, Supriyanto, Siregar IZ, Prasetyo LB, Istomo. 2022. Estimating carbon stocks of three traditional agroforestry systems and their relationships with tree diversity and stand density. Biodiversitas 23: 6137-6146. One of the important sectors as a strategy for climate resilience and low carbon development in Indonesia is Forestry and Other Land Uses (FOLU) including the agroforestry sector. Carbon stock and tree diversity in an ecosystem are dynamic over time and still need to be investigated. This study was aimed: i) to estimate aboveground carbon stocks in the traditional agroforestry of Mount Halimun Salak National Park (MHSNP), in Kampung Birang and Kampung Merabu, East Kalimantan, as well as ii) to analyze the correlation between carbon stock with tree diversity and stand density in traditional agroforestry of Mount Halimun Salak National Park (MHSNP), in Kampung Birang and Kampung Merabu, East Kalimantan. The total plots were 75 plots (a plot size of 50x50 m), and carbon stock estimation was focused on pole and tree levels. The average carbon stock in the traditional zone of MHSNP, Kampung Birang, and Kampung Merabu respectively was 51.02 Mg C/ha, 96.25 Mg C/ha, and 82.17 Mg C/ha. The carbon stock in traditional agroforestry of all study sites was very significantly affected by the basal area (m2/ha) (p-val<0.05) with a strong correlation (r = 80% and 97%). The carbon stock was affected by stand density (p-val<0.1) with a very low correlation (r = 27.3%). The carbon stock was very significantly affected by total species (p-val<0.05). However, it had a weak correlation (r = 28.0%). In agroforestry systems, how to manage the agroforestry, socio-economic aspects, ecological site, and market are the main factor in species selection and species maintenance by landowners that indirectly influence biodiversity conservation effort and carbon stock value. The agroforestry system has the potential to become a target and priority location for Indonesia’s FOLU Net Sink 2030 by providing non-timber forest products, which can avoid leakage in forest conservation efforts and carbon stock.